Maintaining Growth and Sustainable Strategy In Brown Sugar Business, and The Investment Financing Alternative Decision (Case Study: CV. Delovry Sukses Gemilang) - Ariyani, Laurentia Nindita; Siahaan, Uke MMP (The Indonesian Journal of Business Administration, 2013)
CV. Delovry Sukses Gemilang (CV. DSG) is a brown sugar supplier from manufacturers in Maron Village, Blitar, to the warehouse of distributors which is located in Tambun, Bekasi. In doing the business, CV. DSG provides the working capital to the collectors in Blitar to produce and pack the brown sugar. Fluctuating commodity prices of sugar cane leads CV. DSG to be difficult to continually maintain the business and shipping costs which is a way further from Blitar to Bekasi. These issues lead CV. DSG to be difficult to compete with the other brown sugar suppliers from other regions with a closer mileage from Bekasi. To grow and maintain its business, CV. DSG uses the PRIME analysis to identify the existing opportunities. After CV. DSG drafts a business strategy namely short-term strategy (distributors) in 2013, medium-term (factory build), long term (plant cane), the company then invents the scenario analysis on the influential factors that will affect the sugar business generally. The scenario analysis is made on each feasibility study with the proportion of the debt: equity 60%: 40%. In addition, CV. DSG also conducts a feasibility study of the alternative funding to 40% the proportion of equity. From the calculation of the feasibility study by considering the payback period criteria 6 years, NPV IDR 891.417.628, IRR 28,94%, ROI 18,35%, ROE 45,88%, BBP 22,60% and the capacity 2,53, it is shown that the business strategy of CV. DSG in the brown sugar field is feasible and the funding is completed. Key words: brown sugar business, business strategy, Scenario analysis, Feasibility study, Alternative investment.